The effect of gender on disease activity and clinical characteristics in patients with axial psoriatic arthritis. Issue 4 (4th July 2021) - Nas, Kemal; Kiliç, Erkan; Tekeoğlu, İbrahim and Keskin, Yaşar and Çevik, Remzi and Sargin, Betül and Acer Kasman, Sevtap and Alkan, Hakan and Sahin, Nilay and Cengiz, Gizem and Cüzdan, Nihan and Albayrak Gezer, İlknur and Keskin, Dilek and Mülkoglu, Cevriye and Reşorlu, Hatice and Ataman, Şebnem and Bal, Ajda and Baykul, Merve and Duruöz, Mehmet Tuncay and Küçükakkaş, Okan and Yurdakul, Ozan Volkan and Alkan Melikoğlu, Meltem and Ayhan, Fikriye Figen and Bodur, Hatice and Çaliş, Mustafa and Çapkin, Erhan and Devrimsel, Gül and Gök, Kevser and Hizmetli, Sami and Kamanlı, Ayhan and Kocabaş, Hilal and Kutluk, Öznur and Şen, Nesrin and Şendur, Ömer Faruk and Toprak, Murat and Tolu, Sena and Tuncer, Tiraje
Abstract: Objectives: In this study, we aimed to evaluate the effect of gender on clinical findings, disease activity, functional status and quality of life in patients with axial involvement in Turkey. Methods: Patients with PsA who met the CASPAR classification criteria were enrolled consequently in this cohort. Turkish League Against Rheumatism (TLAR)-Network was formed with the participation of 25 centres. The demographic variables, fatigue, diagnostic delay, the beginning of peripheral arthritis, enthesitis, dactylitis and spine involvement, inflammatory low back pain, BASFI, HAQ, HAQ-s, visual analogue scale-pain (VAS-pain), anxiety, depression and disease activity parameters (ESR, DAS28, BASDAI) were recorded. Axial involvement was assessed according to clinical and radiological data according to modified New York (MNYC) or Assessment of SpondyloArthritis international Society (ASAS) criteria. Results: A total of 1018 patients with PsA were included in this study. Of the 373 patients with axial involvement, 150 were male (40.2%) and 223 (59.8%) were female. Spondylitis was detected in 14, 7% of men and 21, 9% of women in all patients. Pain score (VAS) ( p < .002), fatigue ( p < .001), ESR ( p < .001), DAS28 ( p < .001), BASDAI score ( p < .001), PsAQoL ( p < .001), HAQ score ( p < , 01), HAQ-S score ( p < .001), anxiety ( p < .001), depression ( p < .024), FACIT ( p < .001) and FiRST ( p < .001) scores were statistically significantly worse in women than males with axial PsA. However, quality of life was better ( p < .001) and PASI score ( p < .005) were statistically worse in male patients than in female patients with axial involvement. Conclusion: This study has shown that the burden of disease in axial PsA has significant difference between genders. Disease activity, physical disability, functional limitation, depression and anxiety scores were higher in female patients, while quality of life were better and PASI score were higher in male patients. Therefore, we suggest that new strategies should be developed for more effective treatment of axial PsA in female patients.